Enhancer of zeste homolog 2 (EZH2) inhibitors. Issue 7 (3rd July 2018) - Gulati, Nitya; Béguelin, Wendy; Giulino-Roth, Lisa
Abstract: Dysregulation of the histone methyltransferase EZH2 plays a critical role in the development of a variety of malignancies including B-cell lymphomas. As a result, a series of small molecule inhibitors of EZH2 have been developed and studied in the pre-clinical setting. Three EZH2 inhibitors: tazemetostat (EPZ-6438), GSK2816126 and CPI-1205 have moved into phase I/phase II clinical trials in patients with non-Hodgkin lymphoma and genetically defined solid tumors. Early data from the tazemetostat trials indicate an acceptable safety profile and early signs of activity in diffuse large B-cell lymphoma and follicular lymphoma, including patients with EZH2 wild-type and mutant tumors. In this review, we present the rationale, key pre-clinical and early clinical findings of small molecule EZH2 inhibitors for use in lymphoma as well as future challenges and potential opportunities for combination therapies.